HIV-Infected Individuals on ART With Impaired Immune Recovery Have Altered Plasma Metabolite Profiles. (2nd June 2021) - Nyström, Sofia; Govender, Melissa; Yap, Siew Hwei; Kamarulzaman, Adeeba; Rajasuriar, Reena; Larsson, Marie
Abstract: Background: Multiple host factors may influence immune reconstitution in HIV-infected people after the initiation of suppressive antiretroviral therapy (ART). Aberrant metabolic pathways have been reported in people with HIV (PWH) on ART. We hypothesized that alterations in plasma metabolites were associated with immune recovery following ART. Methods: In this cross-sectional study, the plasma metabolomic profiles of PWH on ART were evaluated. PWH of slow and fast immune recovery were classified by increase in CD4 T cells following 2 years of ART. Targeted plasma metabolite profiling by liquid chromatography–mass spectrometry and gas chromatography–mass spectrometry to determine metabolite signatures for HIV recovery identified >200 metabolites. Results: Notably, indole-3-propionic acid was downregulated during HIV, possibly reflecting impaired gastrointestinal epithelium homeostasis. The most important metabolite discriminating between the PWH with fast and slow immune recovery was cysteine. Upregulated cysteine and cysteine pathways may contribute to redox-balance maintenance and T-cell function in PWH with fast immune recovery. Additionally, serine and glycine metabolism and bile acid biosynthesis were the most perturbed metabolic pathways in PWH. Conclusions: These results provide a starting point for developing biomarker candidates for immune recovery in PWH on ART and provide insight into the interplay of metabolism and immune response in HIV infection.